41.8k views
0 votes
Solve the following a) 2(x + 3)=x-4 b) 4(5x-2)=2(9x + 3)

2 Answers

3 votes

If you find problem, respond

Solve the following a) 2(x + 3)=x-4 b) 4(5x-2)=2(9x + 3)-example-1
User Danmanstx
by
5.7k points
4 votes

Answer:

-10 and 7

Explanation:

a) expand 2(x+3)

=2x+6

write equation again

2x+6=x-4

minus x from both sides

=

2x-x+6=x-x-4

x+6=-4

minus 6 from both sides

x+6-6=-4-6

x=-10

answer for a) is x=10

b) 4(5x-2)=2(9x+3)

expand both sides

20x-8=18x+6

minus 18x from both sides

20x-18x-8=18x-18x+6

2x-8=6

add 8 on both sides

2x-8+8=6+8

2x=14

divide by 2 on both sides to find x

x=7

User Ingo Mi
by
6.2k points